Contextualizing Mansinam’s Gospel Legacy: Forming Papua’s Alpha Generation through Early Childhood Christian Education - Prasetya, Didimus Sutanto B.; Sidabutar, Dewi Lidya; Sakati, Abraham Marsal (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Papua had received the Gospel since 1855, yet continued to experience persistent socio-economic and moral challenges, including poverty, limited access to quality education, and the erosion of cultural values. These realities indicated a theological and developmental disconnect between the region’s Christian identity and its lived social condition. This study aimed to explore how Early Childhood Christian Education (ECCE) could be developed as a transformative response to this gap, particularly for the Alpha Generation growing up in Papua’s multicultural context. Conducted through a descriptive qualitative approach within the socio-religious context of Papua, the study employed theological and pedagogical reflection to analyse how Christian values and Papuan indigenous wisdom can be integrated into early education. Data were collected through literature review, analysis of church-based documents, and contextual educational materials. The findings revealed a critical need for Gospel-centered, culturally grounded ECCE models that promote holistic spiritual, emotional, and moral formation from an early age. The study concluded that a contextual and integrative approach to ECCE could bridge the divide between ritual faith and transformative Christian living. This research contributed a conceptual framework for churches and theological institutions to equip young children with Christlike character, cultural rootedness, and active participation in the renewal of Papuan society.